Mechanism-Driven Performance Limitations in FASnI₃ Perovskite Solar Cells: A SCAPS-1D Study of the ITO/ZnO/FASnI₃/NiO/Pt Architecture - Abi Nurhidayat; Bambang Soegijono (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Lead-free FASnI₃ perovskite solar cells offer a promising route toward environmentally benign photovoltaics, yet their practical performance remains constrained by unresolved loss mechanisms and overly idealized simulation assumptions. This study presents a mechanism-resolved SCAPS-1D analysis of the ITO/ZnO/FASnI₃/NiO/Pt architecture by evaluating the contributions of bulk recombination, interface recombination, resistive losses, and temperature effects within a unified framework. A graded realistic-defect methodology is introduced to bridge the gap between near-ideal simulations and fabrication-relevant conditions. Comprehensive parameter sweeps were performed for absorber energetics, doping concentration, thickness, bulk and interface defect densities, transport-layer properties, series resistance, operating temperature, and back-contact work function, while incorporating Shockley–Read–Hall, radiative, and Auger recombination mechanisms. Under near-ideal low-defect conditions, the optimized device achieves V, mA c, FF = 89.04%, and PCE = 31.90%, representing an upper-bound estimate within the simplified optical model. Under realistic conditions, the efficiency decreases systematically to 28.80% for the typical scenario, 22.57% for the moderate scenario, and 15.06% for the pessimistic scenario. The results establish a clear hierarchy of performance-limiting mechanisms, with bulk and interface Shockley–Read–Hall recombination dominating the efficiency gap, followed by series resistance and thermal effects. These findings provide a transferable mechanism-based framework and practical design guidelines for improving high-efficiency, lead-free FASnI₃ perovskite solar cells beyond idealized simulation conditions.